Plasmacytoid dendritic cells and myeloid cells differently contribute to B-cell-activating factor belonging to the tumor necrosis factor superfamily overexpression during primary HIV infection. (28th January 2016) - Borhis, Gwenoline; Burelout, Chantal; Chaoul, Nada; Smith, Nikaïa; Goujard, Cecile; Meyer, Laurence; Paul, Stephane; Saoudin, Henia; Hosmalin, Anne; Gilbert, Caroline; Herbeuval, Jean-Philippe; Richard, Yolande
Abstract : Background: After describing heightened levels of circulating B-cell-activating factor belonging to the tumor necrosis factor superfamily (BAFF) as well as changes in B-cell phenotype and functions during acute infection by simian immunodeficiency virus, we wanted to determine whether and by which cells BAFF was over-expressed in primary HIV-infected (PHI) patients. Design and methods: We simultaneously examined circulating BAFF levels by ELISA and membrane-bound BAFF (mBAFF) expression by flow cytometry in peripheral blood mononuclear cells of healthy donors and PHI patients followed for 6 months. We also examined whether HIV-1 modifies BAFF expression or release in various myeloid cells and plasmacytoid dendritic cells (pDC) in vitro . Results: Circulating BAFF levels were transiently increased at enrolment. They positively correlated with CXCL10 levels and inversely with B-cell counts. Whereas mBAFF was expressed by most pDC and on a fraction of intermediate monocytes in healthy donors, the frequency of mBAFF + cells significantly increased among nonclassical monocytes and CD1c + dendritic cells but decreased among pDC in PHI patients. In contrast to myeloid cells, pDC never released BAFF upon stimulation. Their mBAFF expression was enhanced by HIV-1, independently of type I IFN. Conclusion: Our findings reveal that the pattern of BAFF expression by myeloid cells and pDC is altered in PHI patients and constitutes a valuable marker of immune activation whose circulating levels correlate with CXCL10 levels. Due to their homing in different tissue areas, pDC and myeloid cells might target different B-cell subsets through their mBAFF expression or soluble BAFF release. Abstract : Supplemental Digital Content is available in the text